MENUMBUHKAN NILAI PENDIDIKAN KARAKTER ANAK SD MELALUI DONGENG (FABEL) DALAM PEMBELAJARAN BAHASA INDONESIA - ERNAWATI, ERNAWATI (TERAMPIL: Jurnal Pendidikan dan Pembelajaran Dasar, 2017)
Character education aims to provide guidance to learners to develop the values and characters that have been embedded in each self consciously either in school or in the neighborhood. The purpose of this study is to interpret the value of character education of the fairy tale (fable) of theto Bahasa. This research design used descriptive qualitative. Source of data in this research is fable. The technique used is purposive sampling. Data validity using triangulation of data sources and theories. Data analysis techniques used data reduction, data presentation, and conclusions. The result of this research is the value of character education on fairy tale (fable) to Bahasa Indonesia learning in elementary school. Keywords:Bahasa Indonesia, character education, fairy tale